Long-term testing of eccentric strength in elite female Austrian ski racers and its relationship to racing performance - Patterson, C.; Perez del Rio, A.; Raschner, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Eccentric leg strength is considered a crucial factor in alpine ski racing success (Hoppeler, 2015). The purpose of this study was to examine long-term isokinetic eccentric leg strength characteristics in elite Austrian female alpine ski racers, and to determine if eccentric strength was related to ski racing performance. Methods: The strength testing data of 23 female members of the Austrian alpine ski team who were tested over 5 consecutive years in preseason fitness tests were examined. The athletes were tested on a Con-Trex leg press for unilateral eccentric leg extension strength (ECC). Range of motion was set at knee angles of 85° to 120°. The FIS points at the end of each of the 5 seasons for the best event of each athlete were used to determine ski racing performance. A repeated measures ANOVA with 2 factors was utilized to test if ECC and FIS points changed over the 5 seasons, and if ECC and FIS points interacted (p < 0.05). Results: The mean FIS points for the group was 12.6 ± 7.2 in season 1, and improved to 9.5 ± 6.8 in season 5. The mean ECC of the group was 29.0 ± 5.0 N.kg-1 in season 1, and 30.2 ± 5.0 N.kg-1 in season 5. ECC did not statistically change over the 5 seasons but performance based on FIS points did significantly change over the 5 seasons. There was no significant interaction between the 2 factors of ECC and FIS points. Discussion: Over the 5 years the athletes improved in their FIS points but isokinetic eccentric leg strength did not change and was not found to effect racing performance. There is very little published research relating strength and power test results to athletic performance (Abernathy, et al, 1995). The complexities of ski racing make this even more difficult. Performances are not only determined by the physical abilities of the athlete. Ski characteristics, ski preparation, start number, and snow conditions are examples of important factors which influence performance but are not related to athlete physical preparation. Isokinetic testing is reliable (Abernathy, et al, 1995). Isokinetic tests can determine limb strength asymmetry, and compare concentric and eccentric strength. The results of unilateral isokinetic strength tests can determine if athletes have muscle structural balance (injury prevention), and if athletes are physically fit after a knee injury, which is unfortunately common in ski racing. However, strength tests have little value in predicting ski racing performance.